How big is your bubble? Characteristics of self-isolating household units ('bubbles') during the COVID-19 Alert Level 4 period in New Zealand: a cross-sectional survey. Issue 1 (28th January 2021) - Kearns, Nethmi; Shortt, Nick; Kearns, Ciléin; Eathorne, Allie; Holliday, Mark; Mackle, Diane; Martindale, John; Semprini, Alex; Weatherall, Mark; Beasley, Richard; Braithwaite, Irene
Abstract : Objective: To characterise the self-isolating household units (bubbles) during the COVID-19 Alert Level 4 lockdown in New Zealand. Design, setting and participants: In this cross-sectional study, an online survey was distributed to a convenience sample via Facebook advertising and the Medical Research Institute of New Zealand's social media platforms and mailing list. Respondents were able to share a link to the survey via their own social media platforms and by email. Results were collected over 6 days during Alert Level 4 from respondents living in New Zealand, aged 16 years and over. Main outcomes measures: The primary outcome was the mean size of a self-isolating household unit or bubble. Secondary outcomes included the mean number of households in each bubble, the proportion of bubbles containing essential workers and/or vulnerable people, and the mean number of times the home was left each week. Results: 14 876 surveys were included in the analysis. The mean (SD) bubble size was 3.58 (4.63) people, with mean (SD) number of households 1.26 (0.77). The proportion of bubbles containing one or more essential workers, or one or more vulnerable persons was 45.3% and 42.1%, respectively. The mean number of times individual bubble members left their home in the previous week was 12.9 (12.4). Bubbles that contained at least one vulnerable individual had fewer outings over the previous week compared with bubbles that did not contain a vulnerable person. The bubble sizes were similar by respondent ethnicity. Conclusion: In this New Zealand convenience sample, bubble sizes were small, mostly limited to one household, and a high proportion contained essential workers and/or vulnerable people. Understanding these characteristics from a country which achieved a low COVID-19 infection rate may help inform public health interventions during this and future pandemics.